2017
DOI: 10.1002/smll.201700564
|View full text |Cite
|
Sign up to set email alerts
|

pH Sensing Properties of Flexible, Bias‐Free Graphene Microelectrodes in Complex Fluids: From Phosphate Buffer Solution to Human Serum

Abstract: Advances in techniques for monitoring pH in complex fluids could have significant impact on analytical and biomedical applications ranging from water quality assessment to in vivo diagnostics. We developed flexible graphene microelectrodes (GEs) for rapid (< 5 seconds), very low power (femtowatt) detection of the pH of complex biofluids. The method is based on real-time measurement of Faradaic charge transfer between the GE and a solution at zero electrical bias. For an idealized sample of phosphate buffer sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…From Figure 2b, we see that the Faradaic current for 0.2 pM enkephalin decreased gradually over tens of minutes and saturated after more than 30 min, which is ascribed to an increase in R ct caused by enkephalin binding to wsMOR on the graphene microelectrode so that charge transfer sites were physically blocked. 16 In contrast, for a target concentration of 22 nM, the current decreased much more quickly and saturated after about 6 min. To quantify the binding kinetics, we fit the current i ( t ) with a single-time relaxation model 33 describing ligand−receptor binding: i(t)=iA(c)iB(c)(1et/τ) where i A (c) is an offset current at t = 0, τ is the saturation time constant, and i A ( c ) − i B ( c ) is the saturation current for long times as the system reaches equilibrium (for practical purposes, this requires t ≥ 3τ).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…From Figure 2b, we see that the Faradaic current for 0.2 pM enkephalin decreased gradually over tens of minutes and saturated after more than 30 min, which is ascribed to an increase in R ct caused by enkephalin binding to wsMOR on the graphene microelectrode so that charge transfer sites were physically blocked. 16 In contrast, for a target concentration of 22 nM, the current decreased much more quickly and saturated after about 6 min. To quantify the binding kinetics, we fit the current i ( t ) with a single-time relaxation model 33 describing ligand−receptor binding: i(t)=iA(c)iB(c)(1et/τ) where i A (c) is an offset current at t = 0, τ is the saturation time constant, and i A ( c ) − i B ( c ) is the saturation current for long times as the system reaches equilibrium (for practical purposes, this requires t ≥ 3τ).…”
Section: Resultsmentioning
confidence: 96%
“…22 The charge transfer rate, ∼pC/s, was thus primarily determined by the charge transfer resistance R ct , which is independent of ionic strength. 16 Charge transferred from the solution to graphene accumulated on the feedback capacitor, C f , of the electrometer to produce the readout voltage. For graphene microelectrodes, the effective potential that drives the spontaneous Faradaic current decays logarithmically with increasing ionic strength, 15 instead of the much faster exponential decrease that is characteristic of transistor-based devices.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PBS solution was prepared before the experiment. Since the graphene charge-transfer current is associated with the hydrolysable groups at graphene defects and the pH of the liquid through the Langmuir–Freundlich isotherm 32 , the pH for the blood/PBS was precisely measured and well-controlled in our experiment.…”
Section: Methodsmentioning
confidence: 99%
“…[11,160,[208][209][210] F-FET-based biochemical sensors could provide in situ monitoring of the sweat compositions in a noninvasive way. [211] Considering the complexity of sweat compositions, numerous sensors have been reported toward different ingredients, including pH sensors, [47,147,210,[212][213][214][215][216][217] ion sensors, [47,147,[218][219][220][221][222][223] glucose sensors, [21,45,48,159,[224][225][226] lactate sensors, [227] etc. Based on WO 3 NP, Santos et al [212] reported a representative F-FET-based pH sensor for in vivo applications (Figure 12e).…”
Section: F-fet Sensors Toward Health Monitoringmentioning
confidence: 99%